Preparation of Adsorbents by Pyrolysis of Sludge Mixed With Steel Slag and Study on Adsorption of Chromium Ions in Water - Qi, Xiaowen; Zhou, Enze; Wu, Xuefei; Luo, Siyi; Song, Yanggang (Frontiers in Energy Research, 2022)
In this study, the dewatered sludge from the sewage plant and the open-hearth steel slag of the steel plant are used as raw materials. As two wastes, they were mixed and pyrolyzed to prepare a composite absorbent. Further, the adsorption mechanism of the adsorbent to chromium ions in the sewage is explored. The pyrolysis reaction behavior of sludge mixed with steel slag was studied by the thermogravimetric analysis technology. SEM, BET, and XPS were used to analyze the specific surface area, pore size distribution, and pore structure characteristics of pyrolysis products, respectively. Moreover, a comprehensive analysis of the adsorbent was carried out for the adsorption mechanism of hexavalent chromium ions. The results show that the addition of steel slag promotes the pyrolysis of the sludge in each stage. When the content of steel slag is 80%, the increases of reaction rate are the most obvious with the largest increase of weight loss rate in each stage. The SEM results show that the enrichment of sludge on metal oxides is enhanced in the high-temperature range (600–700°C). Besides, when the content of steel slag is 40–60%, the mixture’s growth rate of the specific surface area can reach 600% and the growth rate of total pore volume can reach 350% (the situations of sludge as the baseline). Regarding the measurement of Cr(VI), the adsorption rate of the steel-slag solution is 50.93% and that of the sludge solution is 69%. However, the adsorption rate can be increased to 95% when the steel slag and sludge were mixed as an adsorption solution. In conclusion, the adsorption mechanism of Cr(VI) by additives is controlled by both physical and chemical processes. The present study provides a theoretical basis and technical support for the scientific and reasonable utilization of sludge and steel slag.